Exploring Consumer’s Reaction in the Bad Gift Situation Across Cultures - Clark, Gracia; Jo, Yooik; Chinchanachokchai, Sydney (My University, 2017)
This study investigated the impacts of bad gift giving across cultures, especially how individualistic (Western, American) vs Collectivistic (Eastern, Asian) consumers react when they receive bad gifts and how it would affect their relationship with the giver.
Color poster with text and graphs.
Keywords: Gift giving; Culture; Cross cultural studies; Posters